Carbon-based dot nanoclusters with enhanced roles of defect states in the fluorescence and singlet oxygen generation. (22nd September 2020) - Hu, Rongjing; Su, Juanxia; Wang, Qian; Chen, Mingming; Jiao, Yajie; Chen, Lichan; Dong, Binhua; Fu, Fengfu; Dong, Yongqiang
Abstract : Carbon-based dot nanoclusters for red emission and high yield singlet oxygen generation are reported for the first time. Abstract : Carbon-based dot nanoclusters (CDCs) are reported for the first time. The morphologies of the obtained CDCs are characterized using transmission electron microscopy and atomic force microscopy. It is found that the CDCs are composed of dozens of carbon-based dots (CDs), which are connected together through the sp 3 -hybridized carbon atoms. When compared with free CDs, the obtained CDCs have higher defect densities. As a result, the UV-vis absorption edge of the CDCs is extended to around 700 nm, and the maximum fluorescence wavelength red-shifts to 570 nm. Furthermore, the CDCs show a high singlet oxygen ( 1 O2 )-generation capability (quantum yield of about 0.13) under visible light irradiation. The long-wavelength emission and the excellent photostability give the obtained CDCs great application potential in cell imaging, and the wide UV-vis absorption band and high 1 O2 -generation capability allow the obtained CDCs to work as effective photosensitizers in photodynamic cancer therapy.